PSMA-Targeted Supramolecular Nanoparticles Prepared From Cucurbit[8]uril-Based Ternary Host–Guest Recognition for Prostate Cancer Therapy - Zhang, Xueyan; Qi, Shaolong; Liu, Dahai; Du, Jianshi; Jin, Jingji (Frontiers in Chemistry, 2022)
Nanomedicines play an important role in cancer therapy, however some drawbacks including unsatisfactory efficacy and side effects arising from indiscriminate drug release retard their clinical applications. Although functionalization of nanomedicines through covalent interactions can improve the pharmacokinetics and efficacy of the loaded drugs, complicated and tedious synthesis greatly limit the exploration of multifunctional nanoparticles. Herein, we utilize a supramolecular strategy to design a nanomedicine for targeted drug delivery through cucurbit[8]uril-based host−guest ternary complexation and successfully prepare prostate-specific membrane antigen (PSMA)-targeted supramolecular nanoparticles encapsulating doxorubicin (DOX). In vitro studies exhibit targeted modification via noncovalent enhance anticancer efficiency of DOX due to the increased cell uptake on account of receptor-mediated endocytosis. This design provides a new strategy for the development of sophisticated drug delivery systems and holds perspective potentials in precise cancer treatments.